Species distribution modelling and predictor variables for species distribution and niche preferences of Pilosocereus leucocephalus group s.s. (Cactaceae). Issue 1 (31st December 2022) - Franco-Estrada, Daniel; Ortiz, Enrique; Villaseñor, José Luis; Arias, Salvador
Abstract : Ecological niche modelling is useful in estimating the environmental requirements of species and, by extension, can also estimate their distributional areas. For most cacti, ecological niche modelling and comparisons between species have only been performed for a set of variables mainly associated with temperature and precipitation. To expand environmental predictors in addition to climate variables, we use topographic and edaphic variables. The aims of this study were to determine which environmental factors influence the geographical distribution of the P. leucocephalus species group s.s. from Mexico and Central America, to build species distribution models, and to assess whether species have different climatic preferences. Based on ecological niche modelling, the main environmental variables that contribute to the distribution of species and the similarities or differences in ecological niches between species were inferred using Maxent and ENMTools. The results revealed that the studied species had different responses to environmental variables, resulting in a unique combination of conditions for each species, showing only six environmental variables in common. In general, variables with the greatest contributions to the models were climatic, followed by edaphic and topographic variables. The results of the quantification of niches between species showed that there was less than 0.5 overlap in Schoener's D values, suggesting niche divergence for the group species but in environments more similar than would be expected by random chance. Although species shared affinities for seasonally dry tropical forests, the importance of preferences for different sets of environmental variables by each species was clear. In addition, niche divergence between closely related species of the P. leucocephalus group s.s. is concordant with the previous delimitation at the species level.